Effects of Ni addition and cyclic sintering on microstructure and mechanical properties of coarse grained WC–10Co cemented carbides. (June 2016) - Zhang, Xiang; Zhou, Jianhua; Lin, Nan; Li, Kun; Fu, Kun; Huang, Ben; He, Yuehui
Abstract: Coarse grained WC–10(Co, Ni) cemented carbides with different Ni contents were fabricated by sintering-HIP and cyclic sintering at 1450 °C. The effects of Ni addition and cyclic sintering on the microstructures, magnetic behavior and mechanical properties of coarse grained WC–10(Co, Ni) cemented carbides have been investigated using scanning electron microscope (SEM), magnetic performances tests and mechanical properties tests, respectively. The results showed that the mean grain size of hardmetals increases from 3.8 μm to 5.78 μm, and the shape factor Pwc decreases from 0.72 to 0.54, with the Ni content increases from 0 to 6 wt.%. Moreover, the W solubility reaches the highest value of 10.33 wt.% when the Ni content is 2 wt.%. The hardness and transverse rupture strength of WC–8Co–2Ni are 1105 HV30 and 2778 MPa, respectively. The cyclic sintering is conducive to increase the WC grain size of WC–10(Co, Ni) and improves the transverse rupture strength of WC–10Co without compromising the hardness of alloys. Highlights: The addition of Ni can promote the growth of WC grain. The cyclic sintering can decrease coercive force and increase the WC grain size. The cyclic sintering can improve the transverse rupture strength of WC–10Co.